Rod Hill and Tony Myatt, The Economics Anti-Textbook: A Critical Thinker’s Guide to Microeconomics (Book Review, Fernwood Publishing Ltd, 2010, 296 p.) - İnan Gidiş (Journal of Islamic Economics)
The book titled "The Economics Anti-Textbook: A Critical Thinker’s Guide to Microeconomics" by Rod Hill and Tony Myatt offers a thorough critique of mainstream microeconomic theories typically presented in traditional textbooks. Structured with a unique approach, each chapter is divided into two sections: the standard text and the critical text title. This dual presentation provides readers with an insightful comparison, where the authors systematically challenge and question the assumptions and narratives commonly found in economic education. The book covers a wide range of topics, including market structures, efficiency, externalities, income distribution, government intervention, and globalization. Notably, the authors debunk the idealization of perfect competition, underscore the importance of externalities and market failures, and scrutinize the marginal productivity theory of income distribution. Furthermore, they analyze the impact of government policies on income redistribution and assess the implications of global trade and globalization. Throughout the book, the authors advocate for a more nuanced and realistic understanding of economic phenomena, urging readers to incorporate ethical considerations, environmental concerns, and power dynamics into their economic analyses. This review provides a comprehensive overview of the book's central themes, emphasizing its unique structure and critical perspective on traditional economic teachings.